The Integration of National and Religious Identity: an Overview of Identity Development in Elementary Schools - Anto, Abdul Haris Fitri; Rahmawati, Dyah Ayu; Martiarini, Nuke (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
Conflicts between groups in Indonesia continue to occur, and diverse studies have attempted to find solutions. As one of the efforts to find these solutions, this research focuses on national identity development as a long-term effort to establish an inclusive national identity to reduce conflict between groups. This study aimed to provide an overview of the national identity development process implemented in public and private elementary schools. The data collection methods employed were observation, interviews, and document analysis. Coding analysis is applied to sort the data and generate themes for the findings. The empirical findings and discussion generate the following conclusions: First, efforts to develop a national identity in public and private elementary schools run comprehensively through cognitive aspects (thoughts, understanding, and principles), affective aspects (attitudes and appreciation), and behavioral aspects (actions and habits). These three aspects are well implemented in the school’s vision, curriculum, subject matter, learning process, non-academic activities, and social life. Second, there are kinds of national identities such as national symbols, religious identity, ethnic identity, and environmental identity. However, national identity and religious identity are boldly emphasized. This is to anticipate the tension between national identity and religious identity, which might stimulate conflict between identities. Therefore, national and religious identities are socialized as two unified identities. Finally, the success rate of the development of national identity in schools varies due to various factors. However, this is a prospect for further research, especially in schools, families, and society.